Pengaruh Beban Kerja dan Work-Life Balance Terhadap Organizational Citizenship Behavior (OCB) dengan Kepuasan Kerja sebagai Variabel Intervening pada Guru di SMP Negeri XYZ Surabaya - Dyah Ayu Pangestu, Almanda; Iryanti, Endang (Jurnal Riset Pendidikan Ekonomi, 2025)
This study aims to examine the influence of workload and work-life balance on Organizational Citizenship Behavior (OCB), with job satisfaction as an intervening variable among teachers at SMP Negeri XYZ Surabaya. Workload and work-life balance are factors that have the potential to affect teachers' job satisfaction and organizational behavior. The research method used is quantitative. Data were collected through questionnaires distributed to teachers at SMP Negeri XYZ Surabaya and analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM) analysis techniques. The results show that workload does not affect OCB, either directly or through job satisfaction. Meanwhile, work-life balance has a significant effect on OCB, both directly and through job satisfaction. This research contributes to the development of theory and human resource management practices in schools.